Спецназ смеется последним: роман / Р. В. Алехин - Алехин Роман Викторович (Чечня, 2007)
Экземпляры: (20170519) / Инвентарный номер: 32929 / Цена: 81.10 / Сис.шифр: Р2 / Авт.знак: А49 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6